2020
DOI: 10.1038/s41467-020-14359-0
|View full text |Cite
|
Sign up to set email alerts
|

Robust ultraclean atomically thin membranes for atomic-resolution electron microscopy

Abstract: The fast development of high-resolution electron microscopy (EM) demands a backgroundnoise-free substrate to support the specimens, where atomically thin graphene membranes can serve as an ideal candidate. Yet the preparation of robust and ultraclean graphene EM grids remains challenging. Here we present a polymer-and transfer-free direct-etching method for batch fabrication of robust ultraclean graphene grids through membrane tension modulation. Loading samples on such graphene grids enables the detection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 46 publications
0
42
0
Order By: Relevance
“…Basically, it is a cleaning technique with water-methanol mixture and centrifugation of the solution for two-three times to isolate large GO flakes, where the majority of GO flakes are 20–70 μm. The previous study by Zheng et al showed that ~20–50 μm GO monolayer functionalized-GO monolayer separations [ 45 , 46 ] could be isolated using low pressure Chemical Vapor Deposition (LPCVD) system successfully. Additionally, NTA modified graphene oxide monolayer was successfully isolated for TEM grids preparation [ 44 ], and the overall size of the GO monolayer is between ~16 and 37 μm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Basically, it is a cleaning technique with water-methanol mixture and centrifugation of the solution for two-three times to isolate large GO flakes, where the majority of GO flakes are 20–70 μm. The previous study by Zheng et al showed that ~20–50 μm GO monolayer functionalized-GO monolayer separations [ 45 , 46 ] could be isolated using low pressure Chemical Vapor Deposition (LPCVD) system successfully. Additionally, NTA modified graphene oxide monolayer was successfully isolated for TEM grids preparation [ 44 ], and the overall size of the GO monolayer is between ~16 and 37 μm.…”
Section: Resultsmentioning
confidence: 99%
“…Our visual inspection, manual screening of individual holes of entire grids (5 grids are screened manually) and statistical analysis suggest that GO monolayer isolated by H 2 O-Methanol is appropriate to coat individual square (50 μm × 50 μm) of holey carbon grids ( Figure 5 ). However, all the GO coated grids were used to determine the cryo-EM structure of proteasome [ 24 , 45 ], GroEL [ 44 ], and apoferritin [ 47 ]. Nevertheless, none of them were able to characterize a 4.6Å map using only ~7800 single particle projections using GO coated holey grids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 18 ] As shown in Figure , the blooming field of 2D materials comprises different structure types and compositions, such as elemental analogs of graphene (EAs), MXenes, TMDs, covalent organic frameworks (COFs), and metal organic frameworks (MOFs), among which EAs, MXenes, and TMDs are introduced preferentially here. [ 19,20 ] Similar to graphene, EAs contain one kind of element, mostly from Groups IV or V of the periodic table. The ones composed of Group IV elements, such as silicene, germanene, and stanene, have the same electronic configurations as graphene.…”
Section: Methodsmentioning
confidence: 99%
“…This partially dsRNA was then mixed with L protein in a 1.1:1 molar ratio at 4°C for 3 hours and the complex LRNA was ultimately resolved on Superdex 200 10/300 GL in a gel filtration buffer (50 mM BTP pH 8.5, 300 mM NaCl). Aliquots of 4 μL purified RVFV LRNA protein at a concentration of~0.4 mg/ml were applied to glow-discharged holey carbon Cu grids (Quantifoil R1.2/1.3) and 4 μL purified RVFV Lapo protein at a concentration of~0.264 mg/ml were applied to glow-discharged homemade graphene grids 44 . Then these two kinds of grids were flash-cooled in liquid ethane using an FEI Vitrobot Mark IV.…”
Section: Cryo-em Sample Preparation and Data Collectionmentioning
confidence: 99%